Multidentate phosphine-coordinated copper trihalide tri-type complex, its synthesis method and application
By designing multi -to -teeton -toothed copper three halogen and three -type cooperatives, a single -line and three -line state jump at the same time, dynamically allocate the excitement, solve the problem of reduced efficiency caused by the accumulation of excitement, improve the efficiency and excitement of electrochemical light emitting devices Sub use rate.
Patent Information
- Application Number
- CN202211203235.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-09-29
AI Technical Summary
Excitons are easily accumulated during the luminescence process of existing electroluminescent materials, resulting in exciton quenching and device efficiency reduction, making it difficult to achieve efficient exciton distribution of dual radiation.
A polydentate phosphine-coordinated copper trihalogen type III complex is designed and synthesized. This complex undergoes a coordination reaction between a polydentate phosphine ligand and copper halide to achieve simultaneous singlet and triplet transitions, dynamically distribute excitons, and reduce excitons. accumulation.
By dynamically allocating excitons, we minimize exciton accumulation, improve the efficiency of electroluminescent devices, suppress efficiency roll-off, and achieve maximum exciton utilization.
Smart Images

Figure BDA0003873226370000031 
Figure BDA0003873226370000032 
Figure BDA0003873226370000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electroluminescence, and in particular relates to a multidentate phosphine-coordinated copper trihalide tri-type complex and a synthesis method thereof, as well as application of the complex in electroluminescent devices. Background Art
[0002] Recently, the Adachi group developed a third-generation OLED using the most advanced thermally excited delayed fluorescence (TADF) technology, in which both singlet and triplet excitons can be trapped to achieve luminescence, and theoretically, the IQE can reach 100%. The main requirement for TADF materials is that there is a small energy gap difference (ΔEST) between their lowest singlet state (S1) and triplet state (T1). When ΔEST is small enough, reverse intersystem crossing (RISC) will occur, and the excitons in the T1 state can be efficiently upconverted to the S1 state through RISC (T1-S1, usually at room temperature), followed by the radiative transition of fluorescence (S1-S0). In general, the RISC rate constant (KRISC) is inversely proportional to ΔEST, resulting in an IQE close to 100%, which indicates that low ΔE ST It is the basic property of efficient TADF materials.
[0003] However, all excitons can be aggregated to radiative T1 or S1 excited states through intersystem crossing or anti-intersystem crossing, achieving 100% exciton utilization. Exciton utilization is fundamental to high-performance OLEDs. For each of the three electroluminescence processes—fluorescence (FL), phosphorescence (PH), and thermally excited delayed fluorescence—emission occurs through only one of these processes. Emission occurs through either singlet or triplet radiative transitions. This single-mode radiation inevitably leads to the accumulation of S1 and T1 excitons in TADF and PH, respectively. This exacerbates exciton quenching due to singlet-triplet and triplet-triplet annihilation (STA and TTA) effects, resulting in reduced device efficiency. Since STA and TTA are proportional to exciton concentration, quenching can be suppressed by reducing the transient exciton concentration. Based on this consideration, dual-channel radiation, where both the S1 and T1 states can radiatively transition during the electroluminescence process, can achieve more efficient and reasonable exciton distribution, thereby improving device performance. Given that T1 state excitons are the majority in the initial state, electroluminescent dyes must undergo rationally controlled intergap and anti-intergap crossing cycles to achieve a truly optimal distribution of S1 and T1 excitons, thereby achieving a balanced and coordinated TADF and PH emission. Therefore, how to construct truly dual-radiative electroluminescent materials remains a major challenge.
[0004] Since copper is an abundant and inexpensive resource, Cu(I) complexes are very attractive and can serve as a promising alternative to noble metal-based luminescent materials. The development of luminescent Cu(I) complexes has been extensively studied in recent years. Ligand-stabilized copper clusters have attracted considerable attention due to their diverse structures and unique optical properties. The high rigidity of the clusters not only suppresses energy loss due to excited-state relaxation but also exhibits excellent thermal and photostability, which is essential for a wide range of applications in bioimaging, biosensing, chemical sensing, stimuli-responsiveness, and emissive coatings.
[0005] The various performances of copper complexes as electroluminescent dyes need to be improved. Therefore, further research is needed to synthesize copper complexes so that their various luminescent properties as electroluminescent dyes can be optimized and improved. Summary of the Invention
[0006] To address the above-mentioned problems, the present invention provides a multidentate phosphine-coordinated copper trihalide tri-type complex. The present invention designs and synthesizes a multidentate phosphine ligand, and obtains the complex by a coordination reaction between the multidentate phosphine ligand and a cuprous halide. The multidentate phosphine-coordinated copper trihalide tri-type complex can simultaneously transition between singlet and triplet states, and achieves dynamic distribution of excitons during electroluminescence, thereby minimizing exciton accumulation, improving device efficiency, suppressing device efficiency roll-off, and achieving maximum exciton utilization during electroluminescence.
[0007] The first aspect of the present invention aims to provide a multidentate phosphine-coordinated copper trihalide tri-type complex, which is obtained by a coordination reaction between a multidentate phosphine ligand and cuprous halide.
[0008] The cuprous halide is selected from one or more of cuprous chloride, cuprous bromide and cuprous iodide.
[0009] The multidentate phosphine ligand is selected from the following ligand compounds:
[0010]
[0011] R is H, alkyl or alkoxy, the alkyl is an alkyl group containing C1-C6 carbon atoms, preferably an alkyl group containing C1-C3 carbon atoms, the alkoxy is an alkoxy group containing C1-C6 carbon atoms, preferably an alkoxy group containing C1-C3 carbon atoms, and R is preferably hydrogen, methyl or methoxy.
[0012] Preferably, the multidentate phosphine ligand is selected from one or more of PhQP, CH3PhQP and CH3OPhQP, preferably selected from PhQP, CH3PhQP or CH3OpPhQP. PhQP, CH3PhQP and CH3OPhQ are:
[0013]
[0014] The second aspect of the present invention aims to provide a method for preparing a polydentate phosphine-coordinated copper trihalide tri-type complex, wherein the method utilizes a polydentate phosphine ligand and cuprous halide to carry out a coordination reaction in a solvent, and post-processes to obtain the polydentate phosphine-coordinated copper trihalide tri-type complex.
[0015] The multidentate phosphine ligand is prepared by reacting a halogenated triphenylphosphine compound with a trihalogenated phosphorus under alkyl lithium catalysis. Specifically, the steps include:
[0016] Step 1: preparing (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine by reacting a dihalogenated benzene compound with a diphenylphosphine halide;
[0017] Step 2: reacting (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine with trihalogenated phosphorus, adding the reactants to a reaction solvent, and reacting in the presence of a catalyst to obtain a reaction solution;
[0018] Step 3: post-treating the reaction solution to obtain a multidentate phosphine ligand.
[0019] The third aspect of the present invention aims to provide a use of the multidentate phosphine-coordinated copper trihalide tri-type complex for preparing an electroluminescent device.
[0020] The fourth aspect of the present invention is to provide a method for preparing an electroluminescent device using the multidentate phosphine-coordinated copper trihalide tri-type complex, which specifically comprises the following steps:
[0021] 1. preparing a conductive anode layer;
[0022] 2. preparing a hole injection layer;
[0023] 3. Preparation of hole transport layer;
[0024] 4. preparing a light-emitting layer;
[0025] 5. preparing an electron transport layer;
[0026] 6. preparing an electron injection layer;
[0027] 7. Prepare a cathode conductive layer, encapsulate, and obtain an electroluminescent device.
[0028] The multidentate phosphine-coordinated copper trihalide tri-type complex provided by the present invention has the following beneficial effects:
[0029] (1) The multidentate phosphine-coordinated copper trihalide tris-type complex of the present invention is used as an electroluminescent dye, and its singlet state and triplet state can transition simultaneously, and the singlet state and triplet state excitons can be utilized simultaneously, and the dynamic distribution of the excitons can be achieved during the electroluminescence process, thereby minimizing the accumulation of excitons, improving the device efficiency, suppressing the efficiency roll-off of the device, and achieving maximum utilization during the electroluminescence process.
[0030] (2) In the present invention, multidentate coordination is used to increase the spin-orbit coupling from the ligand to the metal, and the charge transfer from the halogen to the ligand is regulated by the halogen, thereby enhancing the phosphorescence emission of the copper complex. At the same time, the conjugation degree of the ligand is increased by adding benzene rings to adjust the luminescent color of the copper complex.
[0031] (3) The multidentate phosphine-coordinated copper trihalide tri-type complex electroluminescent dye electroluminescent material prepared by the present invention can realize ultra-low voltage driven electroluminescent devices. The multidentate phosphine-coordinated copper trihalide tri-type complex of the present invention is used as a guest of the light-emitting layer to prepare electroluminescent devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex I of Example 1 of the present invention are shown;
[0033] Figure 2 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex II of Example 2 of the present invention are shown;
[0034] Figure 3 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalide tri-type complex III of Example 3 of the present invention are shown;
[0035] Figure 4 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex IV of Example 4 of the present invention are shown;
[0036] Figure 5 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex V of Example 5 of the present invention are shown;
[0037] Figure 6 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex VI of Example 6 of the present invention are shown;
[0038] Figure 7 The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex VII of Example 7 of the present invention are shown;
[0039] Figure 8The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex VIII of Example 8 of the present invention are shown;
[0040] Figure 9 The ultraviolet spectrum, fluorescence spectrum and phosphorescence spectrum of the multidentate phosphine-coordinated copper trihalogen tri-type complex IX of Example 9 of the present invention are shown. DETAILED DESCRIPTION
[0041] The present invention will be described in detail below through specific embodiments, and the features and advantages of the present invention will become clearer and more distinct with these descriptions.
[0042] The present invention provides a multidentate phosphine-coordinated copper trihalide tri-type complex. This complex is obtained by the reaction and coordination of a multidentate phosphine ligand and a cuprous halide. This complex can be used as an electroluminescent dye and a luminescent guest material to prepare an electrophosphorescent device. The multidentate phosphine-coordinated copper trihalide tri-type complex can simultaneously transition between singlet and triplet states, and achieves dynamic distribution of excitons during the electroluminescence process, thereby minimizing exciton accumulation, improving device efficiency, suppressing device efficiency roll-off, and achieving maximum exciton utilization during the electroluminescence process.
[0043] The multidentate phosphine-coordinated copper trihalide tri-type complex provided by the present invention is obtained by carrying out coordination reaction between a multidentate phosphine ligand and cuprous halide.
[0044] The multidentate phosphine-coordinated copper trihalide tri-type complex has the following structure:
[0045]
[0046] Wherein, X is Cl, Br or I; R is H, alkyl or alkoxy, the alkyl is an alkyl group containing C1-C6 carbon atoms, preferably an alkyl group containing C1-C3 carbon atoms, the alkoxy is an alkoxy group containing C1-C6 carbon atoms, preferably an alkoxy group containing C1-C3 carbon atoms, and R is preferably hydrogen, methyl or methoxy.
[0047] Preferably, the multidentate phosphine-coordinated copper trihalide tri-type complex is:
[0048]
[0049]
[0050] The multidentate phosphine ligand is selected from the following ligand compounds:
[0051]
[0052] R is H, alkyl or alkoxy, the alkyl is an alkyl group containing C1-C6 carbon atoms, preferably an alkyl group containing C1-C3 carbon atoms, the alkoxy is an alkoxy group containing C1-C6 carbon atoms, preferably an alkoxy group containing C1-C3 carbon atoms, and R is preferably hydrogen, methyl or methoxy.
[0053] Preferably, the multidentate phosphine ligand is selected from one or more of PhQP, CH3PhQP and CH3OphQP, preferably selected from PhQP, CH3PhQP or CH3OphQP. PhQP, CH3PhQP and CH3OphQ are:
[0054]
[0055] The multidentate phosphine-coordinated copper trihalide tris-type complex of the present invention, as an electroluminescent dye, can simultaneously transition between singlet and triplet states and achieve dynamic distribution of excitons during the electroluminescence process, thereby minimizing the accumulation of excitons, improving device efficiency, suppressing device efficiency roll-off, and achieving maximum exciton utilization during the electroluminescence process.
[0056] In this invention, multidentate coordination is used to increase the spin-orbit coupling between the ligand and the metal, and halogen is used to regulate the charge transfer from the halogen to the ligand, thereby enhancing the phosphorescence emission of the copper complex. At the same time, the degree of conjugation of the ligand is increased by adding benzene rings to adjust the luminescence color of the copper complex. The multidentate phosphine-coordinated copper trihalogen tri-type complex electroluminescent dye electroluminescent material prepared by this invention can realize high-efficiency electroluminescent devices driven by ultra-low voltage, further improving the current efficiency and external quantum efficiency, with the maximum current efficiency reaching 28.2 cd·A. -1 , the maximum external quantum efficiency can reach 30.2%. It has good thermodynamic stability and a cracking temperature of 386℃-464℃, which improves the luminous efficiency and brightness of organic electroluminescent materials.
[0057] The present invention also provides a method for preparing the polydentate phosphine-coordinated copper trihalide tri-type complex. The method comprises performing a coordination reaction between a polydentate phosphine ligand and cuprous halide in a solvent, and performing post-treatment to obtain the polydentate phosphine-coordinated copper trihalide tri-type complex.
[0058] The multidentate phosphine ligand is selected from one or more of PhQP, CH3PhQP and CH3OPhQP, preferably PhQP, CH3PhQP or CH3OPhQP.
[0059] The multidentate phosphine ligand is prepared by reacting a halogenated triphenylphosphine compound with a trihalogenated phosphorus under alkyl lithium catalysis, wherein the halogenated triphenylphosphine compound is selected from (2-halogenated phenyl) diphenylphosphine or (2-halogenated-4,5-substituted phenyl) diphenylphosphine. Specifically, the following steps are included:
[0060] Step 1: Prepare (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine by reacting a dihalogenated benzene compound with a diphenylphosphine halide.
[0061] The dihalogenated benzene compound is selected from 1,2-dihalogenated benzene, 1,2-dihalogenated-4,5-dialkylbenzene or 1,2-dihalogenated-4,5-dialkoxybenzene, and the halogenated compound is selected from bromo, chloro or iodo, preferably bromo or chloro, more preferably bromo.
[0062] The diphenylphosphonium halide is selected from diphenylphosphonium chloride or diphenylphosphonium bromide.
[0063] In step 1, the reaction is carried out under the catalysis of an alkyllithium, and the alkyllithium is selected from one or more of methyllithium, ethyllithium, propyllithium, isopropyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, pentyllithium, hexyllithium, cyclohexyllithium, tert-octyllithium, n-eicosyllithium, phenyllithium, methylphenyllithium, butylphenyllithium, naphthyllithium and butylcyclohexyllithium, preferably one or more of n-butyllithium, sec-butyllithium and tert-butyllithium, more preferably n-butyllithium.
[0064] The reaction is carried out in a solvent, and the solvent is selected from one or more of ether solvents, ester solvents and ketone solvents, preferably one or more of diethyl ether, methyl ethyl ether, tetrahydrofuran, ethyl acetate, butyl acetate, dimethyl carbonate, methyl butyl ketone, acetone and cyclohexanone, more preferably a mixed solvent of diethyl ether and tetrahydrofuran.
[0065] The molar ratio of the dihalogenated benzene compound to the diphenylphosphonium halide is 1:(0.8-1.8), preferably 1:(0.9-1.5), and more preferably 1:(1-1.3).
[0066] The molar ratio of the dihalogenated benzene compound to the alkyl lithium is 1:(0.8-1.8), preferably 1:(0.9-1.5), and more preferably 1:(1-1.3).
[0067] The molar volume ratio of the dihalogenated benzene compound to the solvent is 1 mmol:(1-9) mL, preferably 1 mmol:(2-7) mL, and more preferably 1 mmol:(3-5) mL.
[0068] The reaction process involves first reacting a dihalogenated benzene compound with an alkyl lithium at -110 to -130°C, then adding a diphenylphosphonium halide dropwise to continue the reaction. The temperature is then raised to 20-28°C and the reaction is continued for 10-14 hours. Ice water is added to quench the reaction, followed by extraction with appropriate amounts of deionized water and dichloromethane (DCM). After drying the organic layer, the solvent is evaporated to yield (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine.
[0069] Step 2: react (2-halogenophenyl)diphenylphosphine or (2-halogeno-4,5-substituted phenyl)diphenylphosphine with trihalogenophosphine, add the resulting mixture into a reaction solvent, and react in the presence of a catalyst to obtain a reaction solution.
[0070] The trihalogenated phosphorus is selected from phosphorus trichloride or phosphorus tribromide.
[0071] The catalyst is an alkyl lithium, selected from one or more of methyl lithium, ethyl lithium, propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, pentyl lithium, hexyl lithium, cyclohexyl lithium, tert-octyl lithium, n-eicosyl lithium, phenyl lithium, methylphenyl lithium, butylphenyl lithium, naphthyl lithium and butylcyclohexyl lithium, preferably one or more of n-butyl lithium, sec-butyl lithium and tert-butyl lithium, more preferably n-butyl lithium.
[0072] In step 2, the reaction solvent is selected from one or more of ether solvents and ketone solvents, preferably selected from one or more of diethyl ether, methyl ethyl ether, tetrahydrofuran, methyl butyl ketone, acetone and cyclohexanone, more preferably tetrahydrofuran.
[0073] The molar ratio of the (2-halogenophenyl)diphenylphosphine or (2-halogeno-4,5-substituted phenyl)diphenylphosphine to the trihalogenophosphorus is 1:(0.2-0.7), preferably 1:(0.4-0.5), and more preferably 1:0.3.
[0074] The molar ratio of the (2-halogenophenyl)diphenylphosphine or (2-halogeno-4,5-substituted phenyl)diphenylphosphine to the alkyllithium is 1:(0.8-1.8), preferably 1:(0.9-1.5), and more preferably 1:(1-1.3).
[0075] The molar volume ratio of (2-halogenophenyl)diphenylphosphine or (2-halogeno-4,5-substituted phenyl)diphenylphosphine to the solvent is 1 mmol:(0.9-4.5) mL, preferably 1 mmol:(1.2-3.5) mL, and more preferably 1 mmol:(1.5-2.5) mL.
[0076] During the reaction, (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine is first reacted with an alkyl lithium at -70 to -85°C, and then a trihalogenated phosphorus is added dropwise to continue the reaction. The temperature is then raised to 20-28°C and the reaction is continued for 10-14 hours. Ice water is added to quench the reaction to obtain a reaction solution.
[0077] Step 3: post-treating the reaction solution to obtain a multidentate phosphine ligand.
[0078] Add appropriate amounts of deionized water and dichloromethane (DCM) to the reaction solution in step 2 for extraction. After the organic layer is dried, the solvent is evaporated to obtain a polydentate phosphine ligand.
[0079] In the reaction of the multidentate phosphine ligand with cuprous halide, the cuprous halide is selected from one or more of cuprous chloride, cuprous bromide and cuprous iodide.
[0080] The molar ratio of the multidentate phosphine ligand to the cuprous halide is 1:(3.5-8.5), preferably 1:(4.5-7.5), more preferably 1:(5.5-6.5), such as 1:6.
[0081] In the reaction of the polydentate phosphine ligand with cuprous halide, the solvent is selected from one or more of a halogenated alkane solvent such as dichloromethane and chloroform, an ether solvent such as tetrahydrofuran and ethylene oxide, and a ketone solvent such as methyl ethyl ketone and acetone, preferably one or more of dichloromethane, chloroform, tetrahydrofuran, ethylene oxide, methyl ethyl ketone and acetone, more preferably dichloromethane.
[0082] The molar volume ratio of the multidentate phosphine ligand to the solvent is 1 mmol:(3-13) mL, preferably 1 mmol:(4-10) mL, and more preferably 1 mmol:(5-7) mL.
[0083] The reaction temperature is 30-55°C, preferably 35-50°C, more preferably 40-45°C; the reaction time is 6-21 hours, preferably 8-18 hours, more preferably 10-15 hours.
[0084] The post-treatment includes spin drying of the solvent and column purification. The column purification is to use a mixed solvent of dichloromethane and petroleum ether as a mobile phase to purify the product by a chromatographic column.
[0085] The present invention also provides a use of the multidentate phosphine coordinated copper trihalide tri-type complex for preparing an electroluminescent device. The light-emitting layer material in the electroluminescent device includes the multidentate phosphine coordinated copper trihalide tri-type complex.
[0086] The present invention also provides an electroluminescent device prepared by using the multidentate phosphine coordinated copper trihalogen tri-type complex.
[0087] The electroluminescent device includes a conductive anode layer, a hole injection layer, a hole transport layer, a light emitting layer, an electron transport layer, an electron injection layer and a cathode conductive layer.
[0088] The present invention also provides a method for preparing an electroluminescent device using the multidentate phosphine-coordinated copper trihalogen tri-type complex, which specifically comprises the following steps:
[0089] 1. preparing a conductive anode layer;
[0090] The conductive anode layer is prepared on a glass or plastic substrate. The conductive anode layer is selected from tin oxide conductive glass (ITO), a transparent conductive polymer such as polyaniline, and a semi-transparent metal such as Au. ITO or a semi-transparent metal is preferred, and ITO is more preferred. Preferably, the conductive anode layer is deposited using a vacuum evaporation method.
[0091] Preferably, the vacuum degree of vacuum evaporation is 1×10 -6 mbar, the evaporation rate is set to 0.1-0.3 nm / s, and the evaporation material is indium tin oxide on the glass or plastic substrate, with a thickness of 1-100 nm for the anode conductive layer, preferably 5-50 nm, more preferably 10-20 nm, such as 10 nm.
[0092] Preferably, the following hole injection layer, hole transport layer, light emitting layer, electron transport layer, electron injection layer and cathode conductive layer are prepared by vacuum evaporation method.
[0093] 2. preparing a hole injection layer;
[0094] The hole injection layer is evaporated on the anode conductive layer, and the thickness of the evaporated layer is 2 to 16 nm, preferably 3 to 12 nm, more preferably 4 to 8 nm, such as 5 nm.
[0095] The hole injection layer material is selected from molybdenum oxide or poly (3,4-ethylenedioxythiophene):polystyrene sulfonate) (PEDOT:PSS), preferably molybdenum oxide, more preferably molybdenum oxide.
[0096] 3. Preparation of hole transport layer;
[0097] The hole transport layer is evaporated on the hole injection layer, and the thickness of the evaporated layer is 45-95 nm, preferably 55-85 nm, more preferably 65-75 nm, such as 70 nm.
[0098] The hole transport layer material is selected from aromatic amine derivatives, such as N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC), preferably 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC).
[0099] 4. preparing a light-emitting layer;
[0100] The light-emitting layer is continuously evaporated on the hole transport layer, and the evaporation thickness is 5-35 nm, preferably 10-30 nm, more preferably 15-25 nm, such as 20 nm.
[0101] The light-emitting layer material includes the multidentate phosphine-coordinated copper trihalogen tris-type complex electroluminescent dye. The light-emitting layer material also includes 9,9'-(1,3-phenyl)di-9H-carbazole (mCP) or bis[2-((oxy)diphenylphosphino)phenyl]ether (DPEPO), preferably 9,9'-(1,3-phenyl)di-9H-carbazole (mCP).
[0102] In the light-emitting layer material, the mass fraction of the multidentate phosphine-coordinated copper trihalide tri-type complex is 1%-20%, preferably 2%-15%, more preferably 3%-10%, such as 3% or 10%.
[0103] 5. preparing an electron transport layer;
[0104] The electron transport layer is evaporated on the light-emitting layer, and the thickness of the evaporated layer is 15-45 nm, preferably 20-40 nm, more preferably 25-35 nm, such as 30 nm.
[0105] The electron transport layer material is selected from one or more of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 1,3,5-tris(3-pyridyl-3-phenyl)benzene (TmPyPB), 4,7-diphenyl-1,10-phenanthroline (Bphen) and dibenzofuran-4,6-bisdiphenylphosphine oxide (DBFDPO), preferably 1,3,5-tris(3-pyridyl-3-phenyl)benzene (TmPyPB).
[0106] 6. preparing an electron injection layer;
[0107] The electron injection layer is evaporated on the electron transport layer, and the thickness of the evaporated layer is 0.6-11 nm, preferably 0.8-8 nm, more preferably 1-5 nm, such as 1 nm.
[0108] The electron injection layer material is selected from lithium tetrakis(8-hydroxyquinoline)borate (LiBq4) or LiF, preferably LiF.
[0109] 7. Prepare a cathode conductive layer, encapsulate, and obtain an electroluminescent device.
[0110] The cathode conductive layer is evaporated on the electron injection layer, and the evaporation thickness is 40-160 nm, preferably 60-140 nm, more preferably 80-120 nm, such as 100 nm.
[0111] The cathode conductive layer material is selected from a single metal cathode or an alloy cathode, such as metal Al.
[0112] Example
[0113] Example 1
[0114] (1) Under nitrogen atmosphere, 236 mg (about 1 mmol) of 1,2-dibromobenzene, 1.8 mL of ether and 1.8 mL of dry THF were added to a three-necked flask to stir the solution. The temperature of the reaction system was lowered to -120°C, and then 1.8 mL of n-butyllithium (n-BuLi) in n-hexane (containing about 1 mmol of n-butyllithium) was added dropwise at a rate of 2 s / d. After the addition was completed, the reaction was continued at -120°C for half an hour. Then, 0.18 mL (about 1 mmol) of diphenylphosphine chloride (Ph2PC1) was added dropwise at a rate of 2 s / d at -120°C. After the addition was completed, the reaction was continued for half an hour. Then, the temperature was raised to 25°C and the reaction was continued for 12 hours. After the reaction was completed, ice water was added to quench the reaction, and then appropriate amounts of deionized water and dichloromethane (DCM) were added for extraction. The organic layer was dried over anhydrous Na2SO4, and the solvent was evaporated to obtain (2-bromophenyl)diphenylphosphine.
[0115] Under a nitrogen atmosphere, 341 mg (about 1 mmol) (2-bromophenyl) diphenylphosphine and 1.8 mL dry tetrahydrofuran (THF) were added to a three-necked flask and the solution was stirred. The reaction temperature was lowered to -78 ° C, and then 1.8 mL of n-butyl lithium (n-BuLi) in n-hexane (containing about 1 mmol n-butyl lithium) was added dropwise at a rate of 2 s / d. Then, the reaction temperature was controlled at -78 ° C, and 0.3 mmol phosphorus trichloride (PCl3) was added dropwise at a rate of 2 s / d. After the addition was completed, the reaction temperature was raised to 25 ° C and the reaction was continued for 12 hours. When the reaction was complete, ice water was added to stop the reaction, and then an appropriate amount of deionized water and DCM were added for extraction. The organic layer was dried over anhydrous Na2SO4, and the solvent was evaporated to obtain the multidentate phosphine ligand PhQP:
[0116]
[0117] (2) 1 mmol of polydentate phosphine ligand PhQP (tris(2-(diphenylphosphonyl)phenyl)phosphane), 6 mmol of CuCl, and 5 ml of DCM were mixed and reacted at 40-45°C for 10 hours. The mixture was evaporated to dryness and purified by column chromatography using a mixed solvent of dichloromethane (DCM) and petroleum ether (PE) as the eluent (the volume ratio of the two was 1:20) to obtain polydentate phosphine-coordinated copper trihalide type III complex I (PhQPCu3Cl3).
[0118] The multidentate phosphine-coordinated copper trihalogen tri-type complex I was tested by nuclear magnetic resonance, and the results were: 1 H NMR (TMS, CDCl3, 400MHz): 7.44-7.47 (m, 24H), 7.15-7.17 (m, 18H).
[0119] The laser desorption ionization time-of-flight mass spectrometry LDI-TOF-MS of the polydentate phosphine-coordinated copper trihalogen tri-type complex Ⅰ was tested, and the results were: m / z (%): 1111.9 (100) [M + ];
[0120] The elemental analysis test results are (C 54 H 42 Cl3Cu3P4) (%): C, 58.34; H, 3.81;
[0121] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex Ⅰ were obtained as follows: Figure 1 shown.
[0122] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide tri-type complex Ⅰ showed that its decomposition temperature was 387℃.
[0123] Preparation of electroluminescent devices using multidentate phosphine-coordinated copper trihalide tri-type complex I as the guest material of the light-emitting layer:
[0124] 1. Place the plastic substrate cleaned with deionized water into a vacuum evaporator with a vacuum degree of 1×10 -6 mbar, and the evaporation rate was set to 0.1 nm s -1 , on a glass or plastic substrate, an anode conductive layer with a thickness of 10 nm is deposited by evaporating indium tin oxide (ITO);
[0125] 2. Vapor-depositing the hole injection layer material MoO3 on the anode conductive layer to obtain a hole injection layer with a thickness of 5 nm;
[0126] 3. Vapor-depositing a hole transport layer material TAPC on the hole injection layer to obtain a hole transport layer with a thickness of 70 nm;
[0127] 4. Evaporating the light-emitting layer material on the hole transport layer. The light-emitting layer material is a mixture of the guest material multidentate phosphine-coordinated copper trihalide tri-type complex I and the host material mCP (wherein the mass fraction of the multidentate phosphine-coordinated copper trihalide tri-type complex I is 3%), with a thickness of 20 nm.
[0128] 5. Evaporating the electron transport layer material TmPyPB on the light-emitting layer to a thickness of 30 nm;
[0129] 6. Vapor depositing the electron injection layer material LiF on the electron transport layer to a thickness of 1 nm;
[0130] 7. A cathode conductive layer with a thickness of 100 nm and made of aluminum was evaporated on the electron injection layer to obtain an electrophosphorescent device (device 1).
[0131] The structure of device 1 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:Ⅰ (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0132] Example 2
[0133] Prepared according to the method of Example 1, except that an equimolar amount of CuBr replaced CuCl to obtain a polydentate phosphine-coordinated copper trihalide tri-type complex II (PhQPCu3Br3)
[0134] Polydentate phosphine-coordinated copper trihalide tri-type complex II 1 H NMR (TMS, CDCl3, 400 MHz) test results are: 7.48-7.52 (m, 24H), 7.19-7.22 (m, 18H);
[0135] The laser desorption ionization time-of-flight mass spectrometry LDI-TOF-MS m / z (%) test result of multidentate phosphine coordinated copper trihalogen type III complex II is: 1243.8 (100) [M+].
[0136] The elemental analysis test results are (C 54 H 42 Br3Cu3P4) (%): C, 52.09; H, 3.40;
[0137] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex II were obtained as follows: Figure 2 shown.
[0138] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide tri-type complex II showed that the cracking temperature of the polydentate phosphine-coordinated copper trihalide tri-type complex II was 386℃.
[0139] An electrophosphorescent device (device 2) was prepared according to the method in Example 1, with the only difference being that in the light-emitting layer material, the multidentate phosphine-coordinated copper trihalide tritype complex I was replaced by the multidentate phosphine-coordinated copper trihalide tritype complex II, and the mass fraction of the multidentate phosphine-coordinated copper trihalide tritype complex II was 10%.
[0140] The structure of device 2 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:Ⅱ (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0141] Example 3
[0142] The electroluminescent dye III (PhQPCu3I3) was prepared according to the method of Example 1, except that CuI was used in an equimolar amount instead of CuCl to obtain a multidentate phosphine-coordinated copper trihalide tri-type complex.
[0143] Polydentate phosphine-coordinated copper trihalide type III complex 1 The test results of H NMR (TMS, CDCl3, 400 MHz) were: 7.50-7.53 (m, 24H), 7.20-7.22 (m, 18H);
[0144] The LDI-TOF-MS test results are: m / z (%): 1385.7 (100) [M+].
[0145] The elemental analysis results are (C 54 H 42 I3Cu3P4) (%): C, 46.79; H, 3.05;
[0146] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen type III complex were obtained as follows: Figure 3 shown.
[0147] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide tri-type complex III showed that the cracking temperature of the polydentate phosphine-coordinated copper trihalide tri-type complex III was 405℃.
[0148] An electrophosphorescent device (device 3) was prepared according to the method of Example 1, with the only difference being that the mass fraction of the multidentate phosphine-coordinated copper trihalide tri-type complex III in the light-emitting layer material was 10%.
[0149] The structure of device 3 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:Ⅲ (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0150] Example 4
[0151] (1) Dissolve 2.5 g of iodine and 230 ml of o-xylene in 500 ml of dichloromethane. Then, react in an ice-water bath at -2 to 2°C for 30 min. Then, add 195 ml of liquid bromine dropwise and react for 24 h. After the reaction is completed, ice water is added to the reaction solution to stop the reaction and precipitate. The precipitate is washed with an aqueous sodium thiosulfate solution and extracted with dichloromethane. After the solvent is removed by rotary evaporation, 1,2-dibromo-4,5-xylene is obtained.
[0152] Under a nitrogen atmosphere, 264 mg (approximately 1 mmol) of 1,2-dibromo-4,5-dimethylbenzene, 1.8 mL (approximately 1 mmol) of diethyl ether, and 1.8 mL of dry THF were added to a three-necked flask and stirred. The temperature of the reaction system was lowered to -120°C, and 0.4 mL of n-butyllithium in n-hexane (n-BuLi) solution (containing approximately 1 mmol of n-butyllithium) was added dropwise at a rate of 2 s / day. Subsequently, 0.18 mL (approximately 1 mmol) of Ph2PC1 was added dropwise at a rate of 2 s / day, while the temperature was maintained at -120°C. After the addition, the reaction was continued for half an hour, and the reaction solution was then warmed to 25°C and allowed to react for 12 hours. Upon completion of the reaction, ice water was added to terminate the reaction, followed by extraction with appropriate amounts of deionized water and DCM. The resulting organic layer was dried over anhydrous Na2SO4, and the solvent was evaporated to yield (2-bromo-4,5-dimethylphenyl)diphenylphosphine.
[0153] Under a nitrogen atmosphere, 369 mg (1 mmol) (2-bromo-4,5-dimethylphenyl) diphenylphosphine and 1.8 mL dry THF were added to a three-necked flask and stirred to dissolve. The reaction solution was lowered to -78 ° C, and 1.8 mL of n-butyl lithium in n-hexane (n-BuLi) solution (containing approximately 1 mmol of n-butyl lithium) was added dropwise at a rate of 2 s / d. Then, the temperature was controlled at -78 ° C, and 0.087 mL (about 1 mmol) of PC13 was added dropwise at a rate of 2 s / d. After the addition was completed, the reaction was continued for half an hour. The reaction was then raised to 25 ° C and the reaction was continued for 12 hours. After the reaction was completed, ice water was added to stop the reaction, and then an appropriate amount of deionized water and DCM were added for extraction. The obtained organic layer was dried over anhydrous Na2SO4, and after evaporating the solvent, the multidentate phosphine ligand CH3PhQP was obtained:
[0154]
[0155] (2) Prepared according to the method of Example 1, the only difference is that an equal molar amount of multidentate phosphine ligand CH3PhQP (tris(2-(diphenylphosphino)phenyl)phosphine) is used instead of multidentate phosphine ligand PhQP (tris(2(diphenylphosphino)-4,5-dimethylphenyl)phosphine), to obtain multidentate phosphine-coordinated copper trihalide type III complex IV (CH3PhQPCu3Cl3).
[0156] Polydentate phosphine-coordinated copper trihalide type III complex Ⅳ 1 H NMR (TMS, CDCl3, 400 MHz) test results are: 7.44-7.47 (m, 18H), 7.11-7.15 (m, 18H), 2.29 (s, 18H);
[0157] The results of LDI-TOF-MS test are: m / z(%): 1196.0(100)[M + ].
[0158] The elemental analysis results are (C 60 H 54 Cu3Cl3P4) (%): C, 60.26; H, 4.55;
[0159] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen type III complex IV were obtained as follows: Figure 4 shown.
[0160] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide tri-type complex IV showed that the cracking temperature of the polydentate phosphine-coordinated copper trihalide tri-type complex IV was 389℃.
[0161] An electrophosphorescent device (device 4) was prepared according to the method of Example 1, with the only difference being that in the light-emitting layer material, the guest material was a multidentate phosphine-coordinated copper trihalogen tri-type complex IV, with a mass fraction of 3%.
[0162] The structure is: ITO / MoOx(5nm) / TAPC(40nm) / mCP:Ⅳ(20nm) / TmPyPB(30nm) / LiF(1nm) / Al.
[0163] Example 5
[0164] It was prepared according to the method of Example 2, except that an equal molar amount of the multidentate phosphine ligand CH3PhQP (tris(2-(diphenylphosphino)phenyl)phosphine) was used instead of the multidentate phosphine ligand PhQP (tris(2(diphenylphosphino)-4,5-dimethylphenyl)phosphine) to obtain the multidentate phosphine-coordinated copper trihalide type III complex V (CH3PhQPCu3Br3).
[0165] 1 H NMR (TMS, CDCl3, 400 MHz) test results are: 7.45-7.48 (m, 18H), 7.12-7.16 (m, 18H), 2.29 (s, 18H);
[0166] The results of LDI-TOF-MS test are: m / z (%): 1327.9 (100) [M + ].
[0167] The elemental analysis results are (C 60 H 54 Cu3Br3P4) (%): C, 54.21; H, 4.09;
[0168] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen type III complex V were obtained as follows: Figure 5 shown.
[0169] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide tri-type complex V showed that the cracking temperature of the polydentate phosphine-coordinated copper trihalide tri-type complex V was 396℃.
[0170] An electrophosphorescent device (device 5) was prepared according to the method in Example 1, with the only difference being that in the light-emitting layer material, the guest material was a multidentate phosphine-coordinated copper trihalogen tri-type complex V, with a mass fraction of 10%.
[0171] The structure of device 5 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:V (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0172] Example 6
[0173] It was prepared according to the method of Example 3, except that an equal molar amount of the multidentate phosphine ligand CH3PhQP (tris(2-(diphenylphosphino)phenyl)phosphine) was used instead of the multidentate phosphine ligand PhQP (tris(2(diphenylphosphino)-4,5-dimethylphenyl)phosphine) to obtain the multidentate phosphine-coordinated copper trihalide tri-type complex VI (CH3PhQPCu3I3).
[0174] 1 H NMR (TMS, CDCl3, 400 MHz) test results: 7.50-7.53 (m, 18H), 7.16-7.20 (m, 18H), 2.29 (s, 18H);
[0175] The results of LDI-TOF-MS test are: m / z(%): 1469.8(100)[M + ].
[0176] The elemental analysis results are (C 60 H 54 Cu3I3P4)(%):C,49.01;H,3.70;The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen tri-type complex VI were obtained as shown in the following figure: Figure 6 shown.
[0177] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide type III complex VI showed that its decomposition temperature was 419℃.
[0178] An electrophosphorescent device (device 6) was prepared according to the method in Example 3, with the only difference being that in the light-emitting layer material, the guest material was a multidentate phosphine-coordinated copper trihalide tri-type complex VI, with a mass fraction of 10%.
[0179] The structure of device 6 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:VI (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0180] Example 7
[0181] (1) Dissolve 2.5 g of iodine and 230 ml of o-phenylenedimethyl ether in 500 ml of dichloromethane. After reacting in an ice-water bath at -2 to 2°C for 30 min, add 195 ml of liquid bromine dropwise and react for 24 h. After the reaction is completed, add ice water to the reaction solution to stop the reaction and precipitate. The precipitate is washed with an aqueous sodium thiosulfate solution and extracted with dichloromethane. The solvent is removed by rotary evaporation to obtain 1,2-dibromo-4,5-dimethoxybenzene.
[0182] Under a nitrogen atmosphere, 296 mg (approximately 1 mmol) of 1,2-dibromo-4,5-dimethoxybenzene, 1.8 mL (approximately 1 mmol) of diethyl ether, and 1.8 mL of dry THF were added to a three-necked flask and stirred to dissolve. The reaction temperature was lowered to -120°C, and 0.4 mL of n-butyllithium in n-hexane (n-BuLi) solution (containing approximately 1 mmol of n-butyllithium) was added dropwise at a rate of 2 s / day. Subsequently, 0.18 mL (approximately 1 mmol) of Ph2PC1 was added dropwise at -120°C at a rate of 2 s / day. After the addition was complete, the reaction was continued for half an hour. The reaction temperature was raised to 25°C, and the reaction was continued for 12 hours. After completion, ice water was added to quench the reaction, followed by extraction with appropriate amounts of deionized water and DCM. The resulting organic layer was dried over anhydrous Na2SO4, and the solvent was evaporated to yield (2-bromo-4,5-dimethoxyphenyl)diphenylphosphine.
[0183] Under a nitrogen atmosphere, 401 mg (about 1 mmol) (2-bromo-4,5-dimethoxyphenyl) diphenylphosphine and 1.8 mL dry THF were added to a three-necked flask and stirred to dissolve. The temperature of the reaction solution was lowered to -78 ° C. 0.4 mL of n-butyl lithium (n-BuLi) in n-hexane (containing about 1 mmol of n-butyl lithium) was added dropwise at a rate of 2 s / d. Then, the temperature was controlled at -78 ° C, and 0.087 mL (about 1 mmol) of PC13 was added dropwise at a rate of 2 s / d. After the addition was completed, the reaction was continued for half an hour, and then the reaction solution was heated to 25 ° C and continued to react for 12 hours. After the reaction was completed, ice water was added to stop the reaction, and then an appropriate amount of deionized water and DCM were added for extraction. The obtained organic layer was dried over anhydrous Na2SO4, and the solvent was evaporated to obtain the ligand CH3OPhQP:
[0184]
[0185] (2) Prepared according to the method of Example 1, the only difference is that an equal molar amount of the multidentate phosphine ligand CH3OPhQP (tris(2-(diphenylphosphino)phenyl)phosphine) is used instead of the multidentate phosphine ligand PhQP (tris(2-(diphenylphosphino)-4,5-dimethoxyphenyl)phosphine), to obtain the multidentate phosphine-coordinated copper trihalide tri-type complex VII (CH3OPhQPCu3Cl3).
[0186] 1 H NMR (TMS, CDCl3, 400 MHz) test results are: 7.44-7.47 (m, 18H), 7.15 (m, 12H), 6.90 (s, 18H), 3.83 (s, 18H);
[0187] The results of LDI-TOF-MS test are: m / z(%): 1292.0(100)[M + ].
[0188] The elemental analysis results are (C 60 H 54 O1Cu3Cl3P4) (%): C, 46.01; H, 4.12;
[0189] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen type III complex VII were obtained as follows: Figure 7 shown.
[0190] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide type III complex VII showed that its cracking temperature was 442℃.
[0191] An electrophosphorescent device (device 7) was prepared according to the method of Example 1, with the only difference being that in the light-emitting layer material, the guest material was a multidentate phosphine-coordinated copper trihalide tri-type complex VII, with a mass fraction of 3%.
[0192] The structure of device 7 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:Ⅶ (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0193] Example 8
[0194] It was prepared according to the method of Example 2, except that an equal molar amount of the multidentate phosphine ligand CH3OPhQP (tris(2-(diphenylphosphino)phenyl)phosphine) was used instead of the multidentate phosphine ligand PhQP (tris(2-(diphenylphosphino)-4,5-dimethoxyphenyl)phosphine) to obtain the multidentate phosphine-coordinated copper trihalide tri-type complex VIII (CH3OPhQPCu3Br3).
[0195] 1H NMR (TMS, CDCl3, 400 MHz) test results are: 7.48-7.51 (m, 18H), 7.15 (m, 12), 6.90 (s, 6H), 3.83 (s, 18H);
[0196] The results of LDI-TOF-MS test are: m / z(%): 1423.8(100)[M + ].
[0197] The elemental analysis results are (C 60 H 54 O1Cu3Br3P4) (%): C, 50.56; H, 3.82;
[0198] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen type III complex VIII were obtained as follows: Figure 8 shown.
[0199] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide type III complex VIII showed that its decomposition temperature was 457℃.
[0200] An electrophosphorescent device (device 8) was prepared according to the method of Example 1, with the only difference being that in the light-emitting layer material, the guest material was multidentate phosphine-coordinated copper trihalide tri-type complex VIII, with a mass fraction of 10%.
[0201] The structure of device 8 is: ITO / MoOx (5nm) / TAPC (70nm) / mCP:Ⅷ (20nm) / TmPyPB (30nm) / LiF (1nm) / Al.
[0202] Example 9
[0203] It was prepared according to the method of Example 3, except that an equal molar amount of the multidentate phosphine ligand PhQP (tris(2-(diphenylphosphino)phenyl)phosphine) was used instead of the multidentate phosphine ligand CH3OPhQP (tris(2-(diphenylphosphino)-4,5-dimethoxyphenyl)phosphine) to obtain the multidentate phosphine-coordinated copper trihalide type III complex IX (CH3OPhQPCu3I3).
[0204] 1 H NMR (TMS, CDCl3, 400 MHz) test results are: 7.62-7.65 (m, 18H), 7.15 (m, 12H), 6.90 (s, 6H), 3.83 (s, 18H);
[0205] The LDI-TOF test results are: m / z (%): 1539.8 (100) [M + ];
[0206] The elemental analysis results are (C60 H 54 O1Cu3I3P4) (%): C, 45.23; H, 3.40;
[0207] The UV spectrum, fluorescence spectrum and phosphorescence spectrum of the polydentate phosphine-coordinated copper trihalogen type III complex IX are as follows: Figure 9 shown.
[0208] Thermogravimetric analysis of the polydentate phosphine-coordinated copper trihalide type III complex IX showed that its decomposition temperature was 464℃.
[0209] An electrophosphorescent device (device 9) was prepared according to the method of Example 1, with the only difference being that in the light-emitting layer material, the guest material was a multidentate phosphine-coordinated copper trihalide tri-type complex IX, with a mass fraction of 10%.
[0210] The structure of device 9 is: ITO / MoOx (5 nm) / TAPC (70 nm) / mCP: IX (20 nm) / TmPyPB (30 nm) / LiF (1 nm) / Al.
[0211] Experimental example
[0212] Experimental Example 1
[0213] Testing of the voltage-current density relationship of the electrophosphorescent devices prepared in Examples 1-9 revealed that the multidentate phosphine-coordinated copper trihalide tri-type complexes I-IX exhibit semiconductor properties. Furthermore, the threshold voltages of the electrophosphorescent devices prepared in Examples 1-9 were 3.5 V, 3.7 V, 3.6 V, 3.5 V, 3.5 V, 4.0 V, 3.0 V, 3.6 V, and 2.8 V, respectively.
[0214] Experimental Example 2
[0215] The voltage-brightness relationship trend of the electrophosphorescent devices prepared in Examples 1 to 9 was tested. It can be seen that the turn-on voltages of the electrophosphorescent devices prepared in Examples 1 to 9 were 3.5V, 3.5V, 3.4V, 3.3V, 3.3V, 3.3V, 3.4V, 3.3V, and 3.4V, respectively.
[0216] Experimental Example 3
[0217] The trend of the relationship between brightness and current efficiency of the electrophosphorescent devices prepared in Examples 1-9 was tested. It can be seen that:
[0218] Device 1 has a brightness of 3 cd·m -2 When the current efficiency reaches the maximum value of 20.1cd·A -1 .
[0219] Device 2 has a brightness of 3 cd·m -2When the current efficiency reaches the maximum value of 22cd·A -1 .
[0220] Device 3 has a brightness of 2.5 cd·m -2 When the current efficiency reaches the maximum value of 21.5cd·A -1 .
[0221] Device 4 has a brightness of 2.2 cd·m -2 When the current efficiency reaches the maximum value of 26.8cd·A -1 .
[0222] Device 5 has a brightness of 2.4 cd·m -2 When the current efficiency reaches the maximum value of 25.2cd·A -1 .
[0223] Device 6 has a brightness of 2.2 cd·m -2 When the current efficiency reaches the maximum value of 28.2cd·A -1 .
[0224] Device 7 has a brightness of 2.7 cd·m -2 When the current efficiency reaches the maximum value of 27.2cd·A -1 .
[0225] Device 8 has a brightness of 2.4 cd·m -2 When the current efficiency reaches the maximum value of 26.3cd·A -1 .
[0226] Device 9 has a brightness of 3.0 cd·m -2 When the current efficiency reaches the maximum value of 24cd·A -1 .
[0227] Experimental Example 4
[0228] The brightness-power efficiency relationship of the electrophosphorescent devices prepared in Examples 1-9 was tested to determine the changing trend.
[0229] Device 1 has a brightness of 3.1 cd·m -2 When the power efficiency reaches the maximum value of 21.4lm·W -1 .
[0230] Device 2 has a brightness of 3.3 cd·m -2 When the power efficiency reaches the maximum value of 22.5lm·W -1 .
[0231] Device 3 has a brightness of 3.0 cd·m -2 When the power efficiency reaches the maximum value of 22lm·W -1 .
[0232] Device 4 has a brightness of 2.0 cd·m -2 When the power efficiency reaches the maximum value of 28.5lm·W -1 .
[0233] Device 5 has a brightness of 4.8 cd·m -2 When the power efficiency reaches the maximum value of 24.2lm·W -1 .
[0234] Device 6 has a brightness of 5.5 cd·m -2 When the power efficiency reaches the maximum value of 30.5lm·W -1 .
[0235] Device 7 has a brightness of 3.0 cd·m -2 When the power efficiency reaches the maximum value of 29.2lm·W -1 .
[0236] Device 8 has a brightness of 3.4 cd·m -2 When the power efficiency reaches the maximum value of 25.4lm·W -1 .
[0237] Device 9 has a brightness of 2.7 cd·m -2 When the power efficiency reaches the maximum value of 28.7lm·W -1 .
[0238] Experimental Example 5
[0239] The changing trend of the relationship between current density and external quantum efficiency of the electrophosphorescent devices prepared in Examples 1-9 was tested. It can be seen that:
[0240] Device 1 at a brightness of 0.5 mA·cm -2 When , the maximum external quantum efficiency of 24.5% is obtained.
[0241] Device 2 has a brightness of 0.6 mA·cm -2 When , the maximum external quantum efficiency of 22.9% is obtained.
[0242] Device 3 has a brightness of 0.4 mA·cm -2 When , the maximum external quantum efficiency of 27.8% is obtained.
[0243] Device 4 has a brightness of 1.1 mA·cm -2 When , the maximum external quantum efficiency of 25.6% is obtained.
[0244] Device 5 has a brightness of 0.9 mA·cm -2 When , the maximum external quantum efficiency of 26.4% is obtained.
[0245] Device 6 has a brightness of 0.8 mA·cm-2 When , the maximum external quantum efficiency of 27.7% is obtained.
[0246] Device 7 at a brightness of 0.5 mA·cm -2 When , the maximum external quantum efficiency of 27.5% is obtained.
[0247] Device 8 has a brightness of 0.9 mA·cm -2 When , the maximum external quantum efficiency of 28.2% is obtained.
[0248] Device 9 has a brightness of 1.2 mA·cm -2 When , the maximum external quantum efficiency of 30.2% is obtained.
[0249] Experimental Example 6
[0250] The electroluminescent properties of the electrophosphorescent devices prepared in Examples 1 to 9 were tested. The electroluminescent peaks of the electrophosphorescent devices prepared in Examples 1 to 9 were 580 nm, 595 nm, 600 nm, 586 nm, 597 nm, 602 nm, 588 nm, 595 nm, and 601 nm, respectively.
[0251] The present invention has been described in detail above with reference to specific embodiments and / or exemplary examples and the accompanying drawings. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will appreciate that various equivalent substitutions, modifications, or improvements may be made to the technical solutions and implementations of the present invention without departing from the spirit and scope of the present invention, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be determined by the appended claims.
Claims
1. A multidentate phosphine-coordinated copper trihalide tri-type complex, wherein the complex is obtained by a coordination reaction between a multidentate phosphine ligand and a cuprous halide. The multidentate phosphine ligand is selected from the following ligand compounds: R is H, alkyl or alkoxy, wherein the alkyl is an alkyl containing C1-C3 carbon atoms, and the alkoxy is an alkoxy containing C1-C3 carbon atoms, The cuprous halide is selected from one or more of cuprous chloride, cuprous bromide and cuprous iodide; The multidentate phosphine-coordinated copper trihalide tri-type complex is: in, X is Cl, Br or I.
2. The complex according to claim 1, characterized in that R is hydrogen, methyl or methoxy.
3. The complex according to claim 1, characterized in that The multidentate phosphine ligand is selected from one or more of PhQP, CH3PhQP and CH3OPhQP, PhQP, CH3PhQP and CH3OPhQ are:
4. The complex according to claim 3, characterized in that The multidentate phosphine ligand is selected from PhQP, CH3PhQP or CH3OPhQP.
5. A method for preparing the multidentate phosphine-coordinated copper trihalide tri-type complex according to any one of claims 1 to 4, characterized in that: The method uses a multidentate phosphine ligand and cuprous halide to carry out a coordination reaction in a solvent, and then post-processes to obtain a multidentate phosphine coordinated copper trihalide tri-type complex; The multidentate phosphine ligand is prepared by reacting a halogenated triphenylphosphine compound with a trihalogenated phosphorus under the catalysis of alkyl lithium; the halogenated triphenylphosphine compound is selected from (2-halogenated phenyl) diphenylphosphine or (2-halogenated-4,5-substituted phenyl) diphenylphosphine.
6. The method according to claim 4, characterized in that The multidentate phosphine ligand is prepared by the following method: Step 1, preparing (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine by reacting a dihalogenated benzene compound with a diphenylphosphine halide; Step 2, reacting (2-halogenated phenyl)diphenylphosphine or (2-halogenated-4,5-substituted phenyl)diphenylphosphine with trihalogenated phosphorus, adding the reactants to a reaction solvent, and reacting in the presence of a catalyst to obtain a reaction solution; Step 3: post-treating the reaction solution to obtain a multidentate phosphine ligand.
7. The method according to claim 6, characterized in that In step 1, the dihalogenated benzene compound is selected from 1,2-dihalogenated benzene, 1,2-dihalogenated-4,5-dialkylbenzene or 1,2-dihalogenated-4,5-dialkoxybenzene, and the halogenated compound is selected from bromo, chloro or iodo.
8. The method according to claim 7, characterized in that In step 1, the halogenated group is bromo or chloro.
9. The method according to claim 6, characterized in that In step 1, The reaction is carried out under the catalysis of an alkyl lithium, and the alkyl lithium is selected from one or more of methyl lithium, ethyl lithium, propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, pentyl lithium, hexyl lithium, cyclohexyl lithium, tert-octyl lithium, n-eicosyl lithium, phenyl lithium, methyl phenyl lithium, butyl phenyl lithium, naphthyl lithium and butyl cyclohexyl lithium; The reaction is carried out in a solvent, and the solvent is selected from one or more of ether solvents, ester solvents and ketone solvents.
10. The method according to claim 9, characterized in that In step 1, The alkyl lithium is one or more of n-butyl lithium, sec-butyl lithium and tert-butyl lithium; The solvent is selected from one or more of ethyl ether, methyl ethyl ether, tetrahydrofuran, ethyl acetate, butyl acetate, dimethyl carbonate, methyl butyl ketone, acetone and cyclohexanone.
11. The method according to claim 10, characterized in that In step 1, The alkyl lithium is n-butyl lithium; The solvent is a mixed solvent of ether and tetrahydrofuran.
12. The method according to claim 6, characterized in that In step 2, The trihalogenated phosphorus is selected from phosphorus trichloride or phosphorus tribromide; The reaction solvent is selected from one or more of ether solvents and ketone solvents.
13. The method according to claim 12, characterized in that In step 2, The reaction solvent is selected from one or more of diethyl ether, methyl ethyl ether, tetrahydrofuran, methyl butyl ketone, acetone and cyclohexanone.
14. The method according to claim 13, characterized in that In step 2, The reaction solvent is tetrahydrofuran.
15. Use of a multidentate phosphine-coordinated copper trihalide tri-type complex according to any one of claims 1 to 4, characterized in that: The invention is used for preparing an electroluminescent device, wherein the light-emitting layer material of the electroluminescent device comprises a multidentate phosphine-coordinated copper trihalogen tri-type complex.
Citation Information
Patent Citations
Cuprous halide cluster compound of furan diphosphine ligand, synthesis method and application thereof, device, ligand thereof and synthesis method thereof
CN112209968A